Desenvolvimento de método alternativo e de suporte à decisão na avaliação de salmonella SPP em farinhas de carnes e ossos bovinos utilizando espectroscopia NIR e carta de controle multivariada baseada na PCA - Santos, Thayná Kawana de Marchi dos (2023)
Bovine meat and bone meal (MBM) is the main slaughtering by-product in slaughterhouses. MBF is the result of cooking residues and is reused in the manufacture of feed for poultry, pigs, dogs, cats, and fish, as it presents nutritional and economic advantages in the formulations. However, the safety of food and the harmlessness of pathogenic microorganisms, such as Salmonella spp., must be guaranteed. Considering that the MBM industries already normally employ spectroscopy in the near-infrared region (NIR) for quality control of other parameters, the evaluation of Salmonella spp. could be incorporated into laboratory routines by NIR. Thus, the objective of this work was the development of a decision support method guided by NIR spectroscopy data and multivariate control charts based on principal component analysis (PCA) in the evaluation of Salmonella spp. in MBM. A total of 350 uncontaminated MBM samples were used in the training step and control chart establishment. Uncontaminated samples of MBM were used in an external validation step (55 samples), while 413 samples contaminated by Salmonella were predicted by the control chart. The achieved results show that the multivariate control charts based on the PCA were efficient for the distinction of bovine meat and bone meal samples absent or present for Salmonella spp. Thus, NIR spectroscopy associated with the PCA-based control chart chemometric tool can be an alternative and a decision support method that can serve as an initial screening tool and reduce the number of analyses through the conventional method.